Antibody drug conjugates of cleavable amino-benzoyl-maytansinoids. Issue 23 (1st December 2020) - Nittoli, Thomas; Delfino, Frank; Kelly, Marcus; Carosso, Serena; Markotan, Thomas; Kunz, Arthur; Chen, Zhaoyuan; Mao, Shu; Shan, Jing; Navarro, Elizabeth; Zhao, Feng; Makonnen, Sosina; et al.
Graphical abstract: Abstract: ADCs based on the natural product maytansine have been successfully employed clinically. In a previous report, ADCs based on hydrophilic non-cell permeable maytansinoids was presented. The authors in this report further explore the maytansine scaffold to develop tubulin inhibitors capable of cell permeation. The research resulted in amino-benzoyl-maytansinoid payloads that were further elaborated with linkers for conjugating to antibodies. This approach was applied to MUC16 tumor targeting antibodies for ovarian cancers. A positive control ADC was evaluated alongside the amino-benzoyl-maytansinoid ADC and the efficacy observed was equivalent while the isotype control ADCs had no effect.